Critical Appraisal of Dantaveshta Through Ayurveda Principle (AYUSHDHARA, 2025)
In Ayurveda the disorders of the oral cavity has been mentioned in Sushruta Samhita in a systemic way under the heading of ‘Mukharoga’. Acharya Sushruta has described the disease ‘Dantaveshta’ under the caption of ‘Dantamulagata Roga’. Acharya Sushruta has mentioned that vitiated Raktadosha gets accumulate in Dantaveshta (gums) and gives rise to Dantamoolagata Raktasrava and Puyasrava (blood and pus discharge from gums) along with Chaladanta (loosening of teeth). Based on signs and symptoms Dantaveshta can be corelated with chronic periodontitis. Poor oral hygiene is the most common cause of periodontal diseases. Chikitsa of Dantaveshta mentioned in Sushruta Samhita such as Raktamokshana, Pratisarana, Gandusha, Nasya etc., break the pathogenesis of the disease. Raktamokshana act as Sodhanakarama which eliminate the vitiated blood from Dantamoola. Pratisarana act as Kapha-Pitta Shamaka, Raktastambhaka, Vranaropana. Effect of Gandusha is mainly Sodhana, Ropana. Nasya helps to maintain integrity of the gingival tissue by its nourishing effect. Acharya Yogartanakara mention the additional Raktapittahara Chikitsa in the disease Dantaveshta which may address systemic vitiation of Doshas.